A needs assessment for a minor eye condition service within Leeds, Bradford and Airedale, UK - Alexander G. Swystun; Christopher J. Davey (BMC, 2019)
Abstract Background There are a number of limitations to the present primary eye care system in the UK. Patients with minor eye conditions typically either have to present to their local hospital or GP, or face a charge when visiting eye care professionals (optometrists). Some areas of the UK have commissioned enhanced community services to alleviate this problem; however, many areas have not. The present study is a needs assessment of three areas (Leeds, Airedale and Bradford) without a Minor Eye Conditions Service (MECS), with the aim of determining whether such a service is clinically or economically viable. Method A pro forma was developed for optometrists and practice staff to complete when a patient presented whose reason for attending was due to symptoms indicative of a problem that could not be optically corrected. This form captured the reason for visit, whether the patient was seen, the consultation funding, the outcome and where the patient would have presented to if the optometrists could not have seen them. Optometrists were invited to participate via Local Optical Committees. Results were submitted via a Google form or a Microsoft Excel document and were analysed in Microsoft Excel. Results Seventy-five percent of patients were managed in optometric practice. Nine and 16% of patients required subsequent referral to their General Practitioner or hospital ophthalmology department, respectively. Should they not have been seen, 34% of patients would have presented to accident and emergency departments and 59% to their general practitioner. 53% of patients paid privately for the optometrist appointment, 28% of patients received a free examination either through use of General Ophthalmic Service sight tests (9%) or optometrist good will (19%) and 19% of patients did not receive a consultation and were redirected to other providers (e.g. pharmacy, accident and emergency or General Practitioner). 88% of patients were satisfied with the level of service. Cost-analyses revealed a theoretical cost saving of £3198 to the NHS across our sample for the study period, indicating cost effectiveness. Conclusions This assessment demonstrates that a minor eye condition service in the local areas would be economically and clinically viable and well received by patients.